DIAGNOSTIC TACTICS FOR CYSTIC LESIONS OF THE PARANASAL SINUS (World Bulletin of Public Health, 2024)
Inflammation of the paranasal sinuses (PNS) is the most common disease in the structure of pathology of the ENT organs. The origin of paranasal sinus cysts is usually associated with a chronic inflammatory process in the nasal cavities, and, according to some authors, the etiology of PNS is more related to allergies, therefore they are considered as a manifestation of allergic sinusitis. The aim of the study is to develop proposals and recommendations aimed at improving the early diagnosis of paranasal sinus cysts. The patients included in the study consisted of 66 women and 87 men (153 in total) aged 18 to 74 years, most of whom were of working age, with an average age of 31.4±3.6 years. To assess the quality of life of the examined patients, we developed an electronic questionnaire "primary questionnaire for comparative diagnosis of diseases", and in order to select patients, we developed an electronic questionnaire "algorithm for early diagnosis of cystic sinusitis" and invited patients to fill them out. Based on a retrospective analysis of clinical cases in which patients have a PNS cyst, the main symptoms characteristic of these pathologies were identified. Computed tomography (CT), performed in coronary, axial and sagittal projections in all patients, has a clear advantage over X-ray examination, since it allows you to more accurately determine the size and composition of all pathological formations, their density (densitometry) , as well as their location in the paranasal sinuses of the nose. Diagnosis of cystic lesions of the accessory nasal cavities should be based on comprehensive diagnostic measures, since they, in turn, have a direct impact on the choice of treatment tactics by patients.
Keywords: Paranasal sinuses; cystic formations; maxillary sinus